A metallofullerene electron donor that powers an efficient spin flip in a linear electron donor-acceptor conjugate - Rudolf, Marc; Feng, Lai; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Journal of the American Chemical Society, 2013)
The dream target of artificial photosynthesis is the realization of long-lived radical ion pair states that power catalytic centers and, consequently, the production of solar fuels. Notably, magnetic field effects, especially internal magnetic field effects, are rarely employed in this context. Here, we report on a linear LuN@I-C-PDI electron donor-acceptor conjugate, in which the presence of the LuN cluster exerts an appreciable electron nuclear hyperfine coupling on the charge transfer dynamics. As such, a fairly efficient radical ion pair intersystem crossing converts the initially formed singlet radical ion pair state, [(LuN@I-C)- PDI], to the corresponding triplet radical ion pair state, [(LuN@I-C)- PDI]. Most notably, the radical ion pair state lifetime of the latter is nearly 1000 times longer than that of the former. © 2013 American Chemical Society.

A multicomponent molecular approach to artificial photosynthesis-the role of fullerenes and endohedral metallofullerenes - Rudolf, Marc; Kirner, Sabrina; Guldi, Dirk Michael (Chemical Society Reviews, 2016)
In this review article, we highlight recent advances in the field of solar energy conversion at a molecular level. We focus mainly on investigations regarding fullerenes as well as endohedral metallofullerenes in energy and/or electron donor-acceptor conjugates, hybrids, and arrays, but will also discuss several more advanced systems. Hereby, the mimicry of the fundamental processes occurring in natural photosynthesis, namely light harvesting (LH), energy transfer (EnT), reductive/oxidative electron transfer (ET), and catalysis (CAT), which serve as a blue print for the rational design of artificial photosynthetic systems, stand at the focalpoint. Importantly, the key processes in photosynthesis, that is, LH, EnT, ET, and CAT, define the structure of this review with the only further differentiation in terms of covalent and non-covalent systems. Fullerenes as well as endohedral metallofullerenes are chosen by virtue of their small reorganization energies in electron transfer processes, on the one hand, and their exceptional redox behaviour, on the other hand.
CRIS-Team Scopus Importer:2023-03-07

An endohedral metallofullerene as a pure electron donor: Intramolecular electron transfer in donor-acceptor conjugates of La2@C80 and 11,11,12,12-tetracyano-9,10-anthra- p -quinodimethane (TCAQ) - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
An endohedral metallofullerene, La@C, is covalently linked to the strong electron acceptor 11,11,12,12-tetracyano-9,10- anthra-p-quinodimethane (TCAQ) by means of the Prato reaction, affording two different [5,6]-metallofulleropyrrolidines, namely 1a and 2a. 1a and 2a were isolated and fully characterized by means of MALDI-TOF mass, UV-vis-NIR absorption, and NMR spectroscopies. In addition, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) corroborated the unique redox character of 2a, that is, the presence of the electron-donating La@C and the electron-accepting TCAQ. Although a weak electronic coupling dictates the interactions between La@C and TCAQ in the ground state, time-resolved transient absorption experiments reveal that in the excited state (i.e., π-π* centered at La@C) the unprecedented formation of the (La@C) -(TCAQ) radical ion pair state evolves in nonpolar and polar media with a quantum efficiency of 33%. © 2012 American Chemical Society.

A paradigmatic change: Linking fullerenes to electron acceptors - Feng, Lai; Rudolf, Marc; Wolfrum, Silke; Troeger, Anna; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Ameri, Tayebeh; Brabec, Christoph; Guldi, Dirk Michael (Journal of the American Chemical Society, 2012)
The potential of Lu N@C and its analogues as electron acceptors in the areas of photovoltaics and artificial photosynthesis is tremendous. To this date, their electron-donating properties have never been explored, despite the facile oxidations that they reveal when compared to those of C . Herein, we report on the synthesis and physicochemical studies of a covalently linked Lu N@C -perylenebisimide (PDI) conjugate, in which PDI acts as the light harvester and the electron acceptor. Most important is the unambiguous evidence-in terms of spectroscopy and kinetics-that corroborates a photoinduced electron transfer evolving from the ground state of Lu N@C to the singlet excited state of PDI. In stark contrast, the photoreactivity of a C -PDI conjugate is exclusively governed by a cascade of energy-transfer processes. Also, the electron-donating property of the Lu N@C moiety was confirmed through constructing and testing a bilayer heterojunction solar cell device with a PDI and Lu N@C derivative as electron acceptor and electron donor, respectively. In particular, a positive photovoltage of 0.46 V and a negative short circuit current density of 0.38 mA are observed with PDI/Ca as anode and ITO/Lu N@C as cathode. Although the devices were not optimized, the sign of the V and the flow direction of J clearly underline the unique oxidative role of Lu N@C within electron donor-acceptor conjugates toward the construction of novel optoelectronic devices. © 2012 American Chemical Society.

Battlement-shaped 1D coordination polymer based on a bis(N-methylimidazole- 2-yl)butadiyne ligand - Waidmann, Thomas; Fritsch, Nico; Tucher, Johannes; Rudolf, Marc; Glaser, Felix; Guldi, Dirk Michael; Burzlaff, Nicolai (Crystengcomm, 2013)
Bis(N-methylimidazole-2-yl)butadiyne (bmib) has been prepared starting from N-methylimidazole following two different pathways. Bmib fluoresces and is capable of forming 1D coordination polymers by clamping together metal units. The molecular structure of a zinc coordination polymer based on bmib and zinc acetate resembles a battlement of a fortress. © 2013 The Royal Society of Chemistry.

Bidirectional Electron Transfer Capability in Phthalocyanine-Sc3N@Ih-C80 Complexes - Trukhina, Olga; Rudolf, Marc; Bottari, Giovanni; Akasaka, Takeshi; Echegoyen, Luis; Torres, Tomas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2015)
To activate oxidative and/or reductive electron transfer reactions, N-pyridyl-substituted Sc3N@Ih-C80 (4) and C60 (3) fulleropyrrolidines have been prepared and axially coordinated to electron-rich (1) or electron-deficient (2) Zn(II)phthalocyanines (Zn(II)Pcs) through zinc-pyridyl, metal-ligand coordination affording a full-fledged family of electron donor-acceptor ensembles. An arsenal of photophysical assays as they were carried out with, for example, 1/4 and 2/4 show unambiguously that a Zn(II)Pc-to-Sc3N@Ih-C80 photoinduced electron transfer takes place in the former ensemble, whereas a Sc3N@Ih-C80-to-Zn(II)Pc electron transfer occurs in the latter ensemble. To the best of our knowledge, this is the first time that a fullerene-based molecular building block shows an electron transfer dichotomy, namely acting both as electron-acceptor or electron-donor, and its outcome is simply governed by the electronic nature of its counterpart. In light of the latter, the present work, which involves the use of Sc3N@Ih-C80, one of the most abundant and easy-to-purify endohedral metallofullerenes, is, on one hand, a paradigmatic change and, on the other hand, an important milestone en-route toward the construction of easy-to-prepare molecular materials featuring switchable electron transfer reactivity.
CRIS-Team Scopus Importer:2023-03-07

Coordinative interactions between porphyrins and C60, La@C 82, and La2@C80 - Tsuchiya, Takahiro; Rudolf, Marc; Wolfrum, Silke; Radhakrishnan, Shankara Gayathri; Aoyama, Ryo; Yokosawa, Yuya; Oshima, Azusa; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Chemistry - A European Journal, 2013)
For the first time, a C derivative (1) and two different lanthanum metallofullerene derivatives, La@CPy (2) and La @CPy (3), that feature a pyridyl group as a coordination site for transition-metal ions have been synthesized and integrated as electron acceptors into coordinative electron-donor/electron-acceptor hybrids. Zinc tetraphenylporphyrin (ZnP) served as an excited-state electron donor in this respect. Our investigations, by means of steady-state and time-resolved photophysical techniques found that electron transfer governs the excited-state deactivation in all of these systems, namely 1/ZnP, 2/ZnP, and 3/ZnP, whereas, in the ground state, notable electronic interactions are lacking. Variation of the electron-accepting fullerene or metallofullerene moieties provides the incentive for fine-tuning the binding constants, the charge-separation kinetics, and the charge-recombination kinetics. To this end, the binding constants, which ranged from log K=3.94-4.38, are dominated by axial coordination, with minor contributions from the orbital overlap of the curved and planar π systems. The charge-separation and charge-recombination kinetics, which are in the order of 10 and 10 s, relate to the reduction potential of the fullerene and metallofullerenes, respectively. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Endohedral metallofullerenes-filled fullerene derivatives towards multifunctional reaction center mimics - Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Feng, Lai; Tsuchiya, Takahiro; Akasaka, Takeshi; Echegoyen, Luis (Chemistry - A European Journal, 2012)
In recent years, endohedral metallofullerenes have attracted tremendous interest not only in physics and chemistry, but also in interdisciplinary areas, such as materials and biological sciences. In this concept article we highlight recent results on different endohedral metallofullerenes based on lanthanides and their derivatives. The chemical and excited state reactivities of endohedral metallofullerenes are discussed for various endohedral clusters. Most important is the part that covers spectroscopic and kinetic assays of reductive and oxidative charge transfer evolving from photoexcited electron donors and electron acceptors, respectively, in a variety of electron donor-acceptor conjugates. Towards this end, we refer to the applications of endohedral metallofullerenes in photovoltaic devices that feature greater efficiency than devices fabricated with empty fullerenes. Herein, we focus mainly on results obtained in the groups of Akasaka, Echegoyen, and Guldi. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Oxidative charge transfer of EMFs, biomedical applications of EMFs, and EMF-based nanomaterials and molecular materials - Lederer, Marcus; Rudolf, Marc; Wolf, Maximilian; Guldi, Dirk Michael; Zhao, Shasha; Lu, Xing; Feng, Lai (CRC Press, 2014)
Fullerenes have been under investigation in different fields of research for nearly 30 years. In September 1985, a group of scientists including Robert Curl, James Heath, Harry Kroto, Yuan Liu, Sean O’Brian, and Richard Smalley discovered fullerenes via mass spectrometry at Rice University in Houston, Texas [1]. This new class of carbon allotropes was termed buckminsterfullerenes because the geodesic domes designed by inventor and architect Buckminster Fuller provided a decisive clue about their structure (Figure 7.1) [2]. A decade later, namely, in 1996, Curl, Kroto, and Smalley were awarded with the Nobel Prize in chemistry for the discovery of fullerenes [1].
CRIS-Team Scopus Importer:2023-03-07

Rates and energetics of intramolecular electron transfer processes in conjugated metallofullerenes - Schubert, Christina; Rudolf, Marc; Guldi, Dirk Michael; Takano, Yuta; Mizorogi, Naomi; Angeles Herranz, M.; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2013)
In this paper, we report on the design, redox potentials, excited state energies and radical ion pair state energies in electron donor-acceptor conjugates comprising the electron-donating π-extended tetrathiafulvalene and several electron-accepting fullerenes. To this end, we contrast an empty fullerene, that is, C, with two endohedral metallofullerenes, that is, open-shell La@C and closed-shell La@C, in terms of charge separation and charge recombination dynamics. © 2013 The Author(s) Published by the Royal Society. All rights reserved.

Stabilizing ion and radical ion pair states in a paramagnetic endohedral metallofullerene/π-extended tetrathiafulvalene conjugate - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
Electron donor-acceptor conjugates of paramagnetic endohedral metallofullerenes and π-extended tetrathiafulvalene (exTTF) were synthesized, characterized, and probed with respect to intramolecular electron transfer involving paramagnetic fullerenes. UV-vis-NIR absorption spectroscopy complemented by electrochemical measurements attested to weak electronic interactions between the electron donor, exTTF, and the electron acceptor, La@C , in the ground state. In the excited state, photoexcitation powers a fast intramolecular electron transfer to yield an ion and radical ion pair state consisting of one-electron-reduced La@C and of one-electron-oxidized exTTF. © 2012 American Chemical Society.

Strong electronic coupling and electron transfer in a Ce2@: I h-C80-H2P electron donor acceptor conjugate - Rudolf, Marc; Feng, Lai; Slanina, Zdenek; Wang, Weiwei; Nagase, Shigeru; Akasaka, Takeshi; Guldi, Dirk Michael (Nanoscale, 2016)
A newly designed electron donor-acceptor conjugate, namely Ce2@Ih-C80-H2P consisting of an endohedral dimetallofullerene Ce2@Ih-C80 and a free-base prophyrin (H2P), has been synthesized and systematically investigated. Basic characterization by means of NMR spectroscopy, steady-state absorption spectroscopy, and electrochemistry points to a folded configuration with sizeable interactions between Ce2@Ih-C80 and H2P. Complementary DFT optimization also results in the same conclusions. Time-resolved absorption spectroscopic investigations corroborate the formation of the (Ce2)-@Ih-C80-(H2P)+ radical ion pair state in non-polar as well as polar media. Overall, the modus operandi is an ultrafast through-space electron transfer enabled by the folded configuration in the ground and excited state.
CRIS-Team Scopus Importer:2023-03-07

Synthesis and Photoinduced Electron-Transfer Reactions in a La2@Ih-C80–Phenoxazine Conjugate - Akasaka, Takeshi; Nakata, Akira; Rudolf, Marc; Wang, Wei-Wei; Yamada, Michio; Suzuki, Mitsuaki; Maeda, Yutaka; Aoyama, Ryo; Tsuchiya, Takahiro; Nagase, Shigeru; Guldi, Dirk Michael (ChemPlusChem, 2017)
A newly designed electron donor–acceptor conjugate consisting of an endohedral dimetallofullerene (La2@Ih-C80) and phenoxazine (POZ) was successfully synthesized under Prato conditions. Our results document that the 1,3-dipolar cycloaddition took place across the [5,6] junction to afford exclusively the corresponding [5,6] cycloadduct. The structure of the conjugate was characterized by means of NMR spectroscopy, absorption spectroscopy, and electrochemical studies. Computational calculations suggest that the electron density of the highest occupied molecular orbital (HOMO) is distributed on the POZ moiety, whereas that of the lowest unoccupied molecular orbital (LUMO) is located at the endohedral La atoms, leading to efficient separation of the HOMO and LUMO in the conjugate. Time-resolved absorption spectroscopic investigations and spectroelectrochemical measurements corroborate the formation of the energetically low-lying (La2@Ih-C80).−–(POZ).+ radical-ion-pair state by means of ultrafast through-space electron transfer.
CRIS-Team Scopus Importer:2022-04-14
Keywords: donor–acceptor systems; electrochemistry; electron transfer; fullerenes; photochemistry

Synthesis and Photophysical Properties of a Sc3N@ C80‐Corrole Electron Donor–Acceptor Conjugate - Liu, Bin; Fang, Hongyun; Li, Xiaofang; Cai, Wenting; Bao, Lipiao; Rudolf, Marc; Plass, Fabian; Fan, Louzhen; Lu, Xing; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
Embedding endohdedral metallofullerenes (EMFs) into electron donor–acceptor systems is still a challenging task owing to their limited quantities and their still largely unexplored chemical properties. In this study, we have performed a 1,3-dipolar cycloaddition reaction of a corrole-based precursor with Sc3N@C80 to regioselectively form a [5,6]-adduct (1). The successful attachment of the corrole moiety was confirmed by mass spectrometry. In the electronic ground state, absorption spectra suggest sizeable electronic communications between the electron acceptor and the electron donor. Moreover, the addition pattern occurring at a [5,6]-bond junction is firmly proven by NMR spectroscopy and electrochemical investigations performed with 1. In the electronically excited state, which is probed in photophysical assays with 1, a fast electron-transfer yields the radical ion pair state consisting of the one-electron-reduced Sc3N@C80 and of the one-electron-oxidized corrole upon its exclusive photoexcitation. As such, our results shed new light on the practical work utilizing EMFs as building blocks in photovoltaics.<br
Keywords: corroles; donor–acceptor systems; fullerenes; metallocycles; photophysics

Taming C60 fullerene: Tuning intramolecular photoinduced electron transfer process with subphthalocyanines - Rudolf, Marc; Trukhina, Olga; Perles, Josefina; Feng, Lai; Akasaka, Takeshi; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2015)
Two subphthalocyanine-C60 conjugates have been prepared by means of the 1,3-dipolar cycloaddition reaction of (perfluoro) or hexa(pentylsulfonyl) electron deficient subphthalocyanines to C60. Comprehensive assays regarding the electronic features-in the ground and excited state-of the resulting conjugates revealed energy and electron transfer processes upon photoexcitation. Most important is the unambiguous evidence-in terms of time-resolved spectroscopy-of an ultrafast oxidative electron transfer evolving from C60 to the photoexcited subphthalocyanines. This is, to the best of our knowledge, the first case of an intramolecular oxidation of C60 within electron donor-acceptor conjugates by means of only photoexcitation.
CRIS-Team Scopus Importer:2023-03-07

Tuning intramolecular electron and energy transfer processes in novel conjugates of La2@C80 and electron accepting subphthalocyanines - Feng, Lai; Rudolf, Marc; Trukhina, Olga; Slanina, Zdenek; Uhlik, Filip; Lu, Xing; Torres, Tomas; Guldi, Dirk Michael; Akasaka, Takeshi (Chemical Communications, 2015)
A series of two conjugates with La2@C80 and subphthalocyanine (SubPc) have been prepared and characterized by means of cyclic voltammetry, absorption, fluorescence, and femtosecond resolved transient absorption spectroscopy. The strong electron-donating character of La2@C80 is essential to power an intramolecular electron-transfer in the La2@C80-SubPc conjugates upon photoexcitation. This journal is
CRIS-Team Scopus Importer:2023-03-07